THE IMPLEMENTATION OF KWL STRATEGY TO IMPROVE STUDENTS READING COMPREHENSION ON ANALYTICAL EXPOSITION TEXT - F12106100, Illusia; Buan, Stevanus; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstrak: Penelitian ini bertujuan untuk meningkatkan pemahaman siswa dalam mengidentifikasi berbagai argument yang disampaikan didalam teks analitikal eksposisi dengan menggunakan know-want-learn sebagai strategi pembelajaran. Metode penelitian yang digunakan yaitu penelitian tindakan kelas yang mana penelitian bertujuan mengatasi masalah yg ditemukan dalam proses pembelajaran. Masalah dalam penelitian ini yaitu kesulitan siswa dalam menemukan berbagai argumen pada teks. Pengambilan data dilakukan dalam tiga siklus dimana setiap siklus terdiri dari planning, acting, observing, and reflecting. Jumlah sampel penelitian ini yaitu 30 siswa dimana data dikumpulkan menggunakan teknik triangulasi yang terdiri dari lembar kerja siswa, tabel observasi dan field notes. Hasil menunjukan bahwa kemampuan siswa dalam memahami berbagai argumen didalam teks analitikal eksposisi meningkat. Skor rata-rata pencapaian siswa pada siklus pertama 48%, siklus kedua 60,6%, dan siklus ketiga 74,3%. Kata kunci : KWL, Analitikal Eksposisi Abstract: The purpose of conducting this research was to improve students reading comprehension on identifying the information given in arguments from analytical exposition text by using know-want-learn as a strategy of learning. This research was conducted as a classroom action research for the purpose of solving the problem that happened in the classroom. The problem in this research was the students difficulties on identifying the information given in the arguments from analytical exposition text. This research was implemented in three cycles and four steps for each cycle, namely: planning, acting, observing and reflecting. The researcher took 30 students as the subjects of research where triangulation was used as the technique of data collecting. It consisted of students worksheet, observation checklist table, and field notes. The finding showed that the students reading comprehension improved. The mean score of students achievement in the first cycle was 48%, in the second cycle was 60.6%, and in the last cycle was 74.3%. Keywords: KWL, Analytical Exposision